ADRIFT: ICELAND, THE CRISIS OF 2008, AND THE CHALLENGE OF REINTEGRATION INTO THE GLOBAL ECONOMY - McDonald, Terry (European Scientific Journal, ESJ, 2015)
The Icelandic experience of boom and subsequent bust in the wake of the 2008 economic crisis is an extreme example of the vulnerabilities and tough choices faced by states in the current global economic order. This paper will use historical analysis, international relations theory, and some aspects of international political economy to illustrate how the crisis came about, was dealt with, and the options faced by Iceland going forward as it seeks to re-integrate into the global economy. In so doing, this should provide a useful analysis for scholars seeking an interdisciplinary explanation of these myriad factors in a single source.